Unusual Twinning Resulting in Chimerism: A Systematic Review on Monochorionic Dizygotic Twins. (27th February 2017) - Peters, Henrike E.; König, Tamar E.; Verhoeven, Marieke O.; Schats, Roel; Mijatovic, Velja; Ket, Johannes C. F.; Lambalk, Cornelis B.
Abstract : Traditionally, it is understood that dizygotic (DZ) twins always have a dichorionic placenta. However, with 8% blood chimerism in DZ twins, placental sharing is probably more common than previously has been recognized. In this article, we will review all available cases of monochorionic dizygotic (MCDZ) twins. A total of 31 twins have been described in literature. A monochorionic diamniotic placenta is reported in all cases. Assisted reproductive technology is responsible for the origin of the pregnancy in 82.1% of the cases. In 15.4% of the sex-discordant twins, a genital anomaly was reported in one of the twins. Chimerism is demonstrable in 90.3% of the twins, leading to various diagnostic difficulties. As this review shows that most MCDZ twins are discovered by accident, it can be argued that it is far more common than has been assumed until now. However, the prevalence is still unclear. Awareness of MCDZ twinning is important, with subsequently correct medical strategies. Similarly, the resulting (blood) chimerism is essential to consider in diagnostic procedures, pre- and postnatally. More research on the effect of placental transfusion between sex-discordant twins is required.